Hydrogen as a Sustainable Fuel: Transforming Maritime Logistics - Seyedeh Azadeh Alavi-Borazjani; Shahzada Adeel; Valentina Chkoniya (Energies)
The marine industry, being the backbone of world trade, is under tremendous pressure to reduce its environmental impact, mainly driven by reliance on fossil fuels and significant greenhouse gas emissions. This paper looks at hydrogen as a transformative energy vector for maritime logistics. It delves into the methods of hydrogen production, innovative propulsion technologies, and the environmental advantages of adopting hydrogen. The analysis extends to the economic feasibility of this transition and undertakes a comparative evaluation with other alternative fuels to emphasize the distinct strengths and weaknesses of hydrogen. Furthermore, based on case studies and pilot projects, this study elaborates on how hydrogen can be used in real-world maritime contexts, concluding that the combination of ammonia and green hydrogen in hybrid propulsion systems presents increased flexibility, with ammonia serving as the primary fuel while hydrogen enhances efficiency and powers auxiliary systems. This approach represents a promising solution for reducing the shipping sector’s carbon footprint, enabling the industry to achieve greater sustainability while maintaining the efficiency and scalability essential for global trade. Overall, this work bridges the gap between theoretical concepts and actionable solutions, therefore offering valuable insights into decarbonization in the maritime sector and achieving global sustainability goals.